2022
DOI: 10.3389/fpubh.2022.933075
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of a COVID-19 outbreak in Nanjing, Jiangsu province, China

Abstract: ObjectivesSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineage B.1.617.2 (also named the Delta variant) was declared as a variant of concern by the World Health Organization (WHO). This study aimed to describe the outbreak that occurred in Nanjing city triggered by the Delta variant through the epidemiological parameters and to understand the evolving epidemiology of the Delta variant.MethodsWe collected the data of all COVID-19 cases during the outbreak from 20 July 2021 to 24 August 2021 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Thirty-one studies [ 29 – 59 ] were included in this review (Table S 1 ). Studies included 17 research articles [ 29 , 32 , 34 , 35 , 40 , 42 , 43 , 45 – 48 , 50 , 53 55 , 57 , 59 ], eight brief communications [ 30 , 31 , 33 , 36 , 39 , 51 , 52 , 58 ], three letters [ 37 , 38 , 41 ], and three reports [ 44 , 49 , 56 ]. Studies were from Belgium [ 33 ], Brazil [ 37 ], China [ 34 36 , 42 , 44 , 45 , 49 51 , 53 57 , 59 ], Germany [ 29 ], Japan [ 46 ], Netherlands [ 30 ], Singapore [ 38 , 52 ], South Korea [ 32 , 39 41 , 58 ], Spain [ 31 ], U.K. [ 47 ], and U.S.A. [ 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-one studies [ 29 – 59 ] were included in this review (Table S 1 ). Studies included 17 research articles [ 29 , 32 , 34 , 35 , 40 , 42 , 43 , 45 – 48 , 50 , 53 55 , 57 , 59 ], eight brief communications [ 30 , 31 , 33 , 36 , 39 , 51 , 52 , 58 ], three letters [ 37 , 38 , 41 ], and three reports [ 44 , 49 , 56 ]. Studies were from Belgium [ 33 ], Brazil [ 37 ], China [ 34 36 , 42 , 44 , 45 , 49 51 , 53 57 , 59 ], Germany [ 29 ], Japan [ 46 ], Netherlands [ 30 ], Singapore [ 38 , 52 ], South Korea [ 32 , 39 41 , 58 ], Spain [ 31 ], U.K. [ 47 ], and U.S.A. [ 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Distributions used to fit the serial interval data were gamma (15 studies [ 29 , 36 , 44 47 , 52 – 59 ]), normal (five studies [ 32 34 , 39 , 40 ]), Weibull (three studies [ 42 , 49 , 50 ]), Gaussian (one study [ 37 ]), and skewed normal (one study [ 38 ]); the distribution was unspecified for four studies [ 30 , 31 , 35 , 41 ]. All studies but four reported mean and SD for serial interval.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SARS-CoV-2 Omicron variant spread rapidly nationwide since November 2022, seriously affecting the health of residents. In previous studies, the factors associated with the infection rate of COVID-19 might include socio-demographic factors such as gender, age, and occupation, but the results were not entirely consistent ( 8 , 9 ), whereas vaccination has presented a certain protective effect against COVID-19 ( 10 , 11 ). And in the few studies of reinfection in China, the factors influencing reinfection rates were similar to those of initial infection ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 86%